99.4k views
5 votes
Which of the following is the correct factorization of the polynomial below 2x^2-12x+18

User Kamartem
by
5.1k points

2 Answers

4 votes

Answer:


\large\boxed{2x^2-12x+18=2(x-3)(x-3)=2(x-3)^2}

Explanation:


2x^2-12x+18=(2)(x^2)-(2)(6x)+(2)(9)\\\\=(2)(x^2-6x+9)=2(x^2-2(x)(3)+3^2)\\\\\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\=2(x-3)^2=2(x-3)(x-3)

User Werupokz
by
5.5k points
5 votes

Answer:

It can be written as 2(x-3)(x-3) or 2(x-3)².

Explanation:

2x² - 12x + 18 = 2(x² - 6x +9) = 2(x-3)(x-3) =2(x-3)²

User Pavel Perevezencev
by
5.9k points